Relationship of Structural Characteristics to Biomechanical Profile in Normal, Keratoconic, and Crosslinked Eyes. Issue 7 (July 2015) - Viswanathan, Deepa; Kumar, Nikhil L.; Males, John J.; Graham, Stuart L.
Abstract : Purpose: To evaluate the correlation of corneal biomechanical parameters with structural characteristics in normal, keratoconic, and collagen crosslinked eyes. Methods: A prospective observational study that included 50 normal, 100 keratoconic, and 25 crosslinked eyes. All eyes were imaged using a Scheimpflug camera and an ocular response analyzer. The main outcome measures analyzed were central corneal thickness (CCT), corneal volume (CV), maximal keratometry (Kmax), corneal hysteresis (CH), and corneal resistance factor (CRF). Results: Significant differences were noted among all 3 groups of eyes for CCT, CV, Kmax, CH, and CRF values ( P < 0.05 by analysis of variance). CH and CRF correlated negatively (CH, r = −0.40; CRF, r = −0.44; both P < 0.0001) with the Pentacam topographic keratoconus classification. Both CH and CRF correlated positively with CCT and CV for the normal, keratoconic, and crosslinked eyes. In contrast, significant negative correlations were observed between CH, CRF, and Kmax in the keratoconic eyes (CH, r = −0.43; CRF, r = −0.53; both P < 0.0001), whereas no association was noted for the normal and crosslinked eyes. Conclusions: CH and CRF are influenced by the corneal structure, with higher values noted in corneas with greater thickness and volume. Corneal biomechanical parameters progressively decrease as the severity of keratoconus increases. After collagen crosslinking, the relationship of the corneal curvature to the biomechanical profile is similar to normal eyes.